UK construction companies’ strategies in the face of business cycles - Ruddock, Les; Kheir, Amir; Ruddock, Steven (International Journal of Strategic Property Management, 2014)
Firms in the construction industry have always had to deal with the challenges of the economic cycle and develop strategies to deal with the resulting fluctuations in their business environment. In the context of the 2008–2011 double-dip recession in the UK, the results of a survey targeting the top one hundred construction companies in the UK are reported here. This research is particularly intended to assess whether the strategies of large companies in the construction sector, when faced with the issues associated with the variation in the economic cycle, have changed since the previous business cycle (i.e. the 1986–1990 boom followed by the 1990–1991 recession). The survey reveals the challenges that companies have faced, reports on company behaviour and on the policies adopted. While there are many similarities between policies adopted during the recessionary periods of the two cycles, the research found notable changes in attitudes towards diversification, human resource management and price bidding. First Publish Online: 18 Sep 2014